2018
DOI: 10.5817/soc2018-1-45
|View full text |Cite
|
Sign up to set email alerts
|

How Ageing and Quality of Life is Influenced by Social Relationships: An Exploration of Rural Midlife Women in Ireland

Abstract: The aim of this article is to examine and contribute to the existing body of knowledge on gendered rural ageing by exploring, from a lifecourse perspective, the pivotal role of social relationships in shaping the quality of life for rural women at mid-life and beyond. Quality of life is examined in relation to the contributing factor of social relationships, and the article further explores concepts that intersect with social relationships to influence quality of life, including those of place, work, and healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
2
2
0
2
Order By: Relevance
“…Furthermore, patients have described their relationships as a core resource in the recovery process ( Schön et al, 2009 ), which might encourage them to focus on their social resources more. This is in line with the finding that meaningful relationships may influence how a person experiences their quality of life and how included they feel socially ( Herbert, 2018 ). Consistent with this position, we found that compared to community members, patients reported a greater desire for change in their meaningful relationships.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, patients have described their relationships as a core resource in the recovery process ( Schön et al, 2009 ), which might encourage them to focus on their social resources more. This is in line with the finding that meaningful relationships may influence how a person experiences their quality of life and how included they feel socially ( Herbert, 2018 ). Consistent with this position, we found that compared to community members, patients reported a greater desire for change in their meaningful relationships.…”
Section: Discussionsupporting
confidence: 88%
“…De Koning et al ( 36 ) argue that volunteering, accompanying others and engaging in sports or exercise were associated with lower social isolation from neighbors, family, and friends. These findings are well-supported by a study conduted in Ireland ( 79 ) which noted the intersectionality between social relationships, place, work, health and quality of life among older women.…”
Section: Theme 2 Social Network and Their Impacts On Loneliness Of Ol...supporting
confidence: 66%
“…However, this study extends Jahoda's model by examining the nuances within each of these elements within a gendered, rural context at the mid-life stage of the lifecourse, as well as highlighting additional latent benefits not discussed in Jahoda's model. In general, participants of this study recognised that paid work offered them the opportunity for improved connectivity (Herbert, 2018), augmented personal identity (Biggs, 2005) and financial agency (Bowling, 2018). Specifically, individual latent benefits of employment reported by participants included: self-esteem, self-confidence, antidote to loneliness, life purpose, economic contribution and constructive use of time.…”
Section: Conclusion and Discussionmentioning
confidence: 99%